Snf2h Drives Chromatin Remodeling to Prime Upper Layer Cortical Neuron Development - Alvarez-Saavedra, Matías; Yan, Keqin; De Repentigny, Yves; Hashem, Lukas E.; Chaudary, Nidhi; Sarwar, Shihab; Yang, Doo; Ioshikhes, Ilya; Kothary, Rashmi; Hirayama, Teruyoshi; Yagi, Takeshi; Picketts, David J. (Frontiers in Molecular Neuroscience, 2019)
Alterations in the homeostasis of either cortical progenitor pool, namely the apically located radial glial (RG) cells or the basal intermediate progenitors (IPCs) can severely impair cortical neuron production. Such changes are reflected by microcephaly and are often associated with cognitive defects. Genes encoding epigenetic regulators are a frequent cause of intellectual disability and many have been shown to regulate progenitor cell growth, including our inactivation of the Smarca1 gene, one of two mammalian orthologues of ISWI. Loss of the Snf2l protein resulted in dysregulation of Foxg1 and IPC proliferation leading to macrocephaly. Here we show that inactivation of the closely related Smarca5 gene encoding the Snf2h chromatin remodeler is necessary for embryonic intermediate progenitor cell expansion and subsequent specification of upper layer neurons. Telencephalon-specific Smarca5 cKO embryos have impaired cell cycle kinetics and increased cell death, resulting in fewer Tbr2+ and FoxG1+ IPCs by mid-neurogenesis. These deficits give rise to adult mice with a dramatic reduction in Satb2+ upper layer neurons, and partial agenesis of the corpus callosum. Mice survive into adulthood but molecularly display reduced expression of the clustered protocadherin-β genes that further contribute to altered dendritic arborization and a hyperactive behavioral phenotype. Our studies provide important new insights into the role of Snf2h-driven chromatin remodeling and brain development.